How does the COVID-19 economic crisis impact resilience? A configurational analysis of the spinoffs - Castelló-Sirvent, Fernando; Peris-Ortiz, Marta; Llopis-Amoro, Malar; Pinazo-Dallenbach, Pablo (My University, 2023)
Spin-offs are companies with a high level of disruption that facilitate University-Society-Business knowledge transfer, promoting innovation and economic development of knowledge-based economies. On the other hand, globalization, climate change and anthropogenic pressure increase the probability of the appearance of community-transmitted pandemics between animals and people. In this context, the study of the conditions that facilitate resilience in companies with a high innovative content are important to guarantee long-term economic development. COVID-19 presents the appropriate conditions for carrying out an exploratory natural experiment that allows the identification, description, and analysis of conditions that facilitated the resilience of spin-offs promoted in a technological university. A database of spin-offs created before COVID-19 in the Universitat Politècnica de València was analyzed. A causal model was proposed and tested with fsQCA to identify the conditions that facilitate the business resilience of this type of startups with a high technological component that link areas of university research with the market. The proposed model defines resilience as the ability of a spin-off to withstand the impact of the shock, calculating differences of natural logarithms of sales in 2020 and 2019. The causal conditions used in the model are TMT Gender Diversity, the Distribution of Added Value to Workers and Ambidexterity (concerning Exploitation and Exploration). The results of this study show the necessary and sufficient conditions for the resilience to environmental shocks of spin-offs from a polytechnic university. This research offers promising lines of development for academics and suggests to policy makers ways to develop public–private initiatives and investment to improve business performance in crisis contexts. The results of this article offer practitioners a useful guide to design strategies that improve the resilience of these types of companies. This exploratory study based on case analysis makes it possible to identify design elements of the strategy that improve resilience before supply crises. A relevant contribution of this research is linked to its managerial implications in the design of strategies to improve resilience in crisis management. The lessons learned and the analysis of best practices can help improve the robustness of new spin offs in a context of crises caused by recurring pandemics.
International Entrepreneurship and Management Journal
Keywords: Spin-off; Resilience; Strategy; Crisis; COVID-19; Campus Mexicali